Preferential consumption of larger fruits of Piper arboreum (Piperaceae) by Carollia perspicillata (Phyllostomidae) in the Brazilian tropical dry forest - Pires, Luís Paulo; Del-Claro, Kleber; Uieda, Wilson [UNESP] (Univ Federal Uberlandia, 2015)
Frugivorous animals may use morphological traits of food items such as size, hardness, shape, color and smell as cues that allow them to assess cost-benefit relationship of foraging activity. Fruit size is an important trait that influences feeding behavior of most frugivores, since there is a functional correlation between fruit size and frugivores'body size. Therefore, size-based preference is fundamental to understand plant-frugivore interactions and seed dispersal. In this sense, we tested the hypothesis of preferential consumption of larger fruits of Piper arboreum by the short-tailed fruit bat Carollia perspicillata in the Brazilian tropical dry forest. Results showed considerable variation in fruit size among and within plants. There was also significant difference in fruit ripening time among plants, which was not related to fruit size. Average size of remaining fruits reduced as they were removed from plants by the bats, which indicates preferential consumption of larger fruits. On the other hand, plant phenology constrained consumption of bigger fruits. Only a small fraction of plant crop was available for consumption each night, regardless of fruit size, which probably coerced bats to feed on smaller fruits as the availability of larger ones decreased. Results suggest that bat preference on fruit size is mediated by plant phenological strategies.

Os frugívoros utilizam as características morfológicas dos frutos tais como tamanho, dureza, forma, cor e cheiro, como pistas para avaliar o custo-benefício da atividade de forrageio. O tamanho dos frutos é uma característica importante que influencia o comportamento alimentar dos frugívoros, já que existe uma correlação funcional entre tamanho do fruto e o do tamanho do frugívoro. Por isso, a seleção do fruto a partir do seu tamanho é um elemento fundamental para a compreensão das interações frugívoro-planta e da dispersão de sementes. Neste sentido, nós testamos a hipótese de consumo preferencial de frutos maiores de Piper arboreum pelo morcego Carollia perspicillata em uma floresta tropical brasileira. Os resultados mostraram ampla variação no tamanho do fruto entre e dentro das plantas parentais. Também houve diferença significativa no tempo de maturação dos frutos entre as plantas, o qual não esteve relacionado com o tamanho do fruto. O tamanho médio dos frutos restantes na planta após a remoção pelos morcegos decresceu, o que indicou o consumo preferencial dos frutos maiores. Por outro lado, a fenologia da planta restringiu o consumo destes frutos. Um número pequeno de frutos maduros esteve disponível para o consumo por noite, independentemente de seu tamanho, o que provavelmente limitou a escolha dos morcegos, obrigando-os a se alimentarem dos frutos menores conforme a disponibilidade dos maiores reduziu-se. Os resultados sugerem que a preferência dos morcegos pelo tamanho dos frutos é mediada pelas estratégias fenológicas das plantas.
Consumo preferencial de frutos maiores de Piper arboreum (Piperaceae) por Carollia perspicillata (Phyllostomidae) em uma floresta tropical brasileira
Keywords: Fruit choice; Frugivory; Seed dispersal; Syndromes; Brazil; Escolha do fruto; Frugivoria; Dispersão de sementes; Síndromes; Brasil